SISTEM INFORMASI E-ARSIP SURAT MASUK DAN SURAT KELUAR PADA KANTOR CAMAT KOTA KISARAN TIMUR - Ayu Amelia Pangesti (Tamilis Synex: Multidimensional Collaboration, 2024)
This information system for incoming and outgoing mail serves to help alleviate this the job of an employee where managing letters is the job of every agendaist The day is carried out in connection with official office activities. Mail Management Entry is carried out starting from receiving the incoming letter, checking it, recording it in the incoming letter book up to filing. Meanwhile, handling outgoing letters starts from concept creation to with delivery. The working system of this information system is divided into two parts, namely Incoming Letters and Letters go out. For incoming agenda letters, just note down the letter number, date of the letter, contents of the letter, attachments to the letterand the purpose of the letter. The computer will automatically save it. Meanwhile in the letter The concept of outgoing letters is the same as incoming letters, so an planner does not need to record them in a book outgoing mail. This system development uses neatbeans software. As is This system is expected to make the work of an agendaist more efficient and effective.